Análisis a los estados financieros de la Cooperativa de Ahorro y Crédito Vicentina Ma-nuel Esteban Godoy Ortega LTDA. COOPMEGO agencia Zamora períodos 2014-2015 - Arias Herrera, Flora Jhuliana (2018)
This thesis work, I take it to effect in order to meet the requirements prior to obtaining the degree in Accounting and Auditing (CPA), at the National University of Loja, thus adjusting to the Regulations Regime Current academic Likewise, it was carried out for the purpose of developing an analysis of the Financial Statements of the Manuel Esteban Godoy Ortega Ltda. Cooperativa de Ahorro y Crédito Vicentina, COOPMEGO, in order to know the economic and financial situation of said institution, through the application of indicators financial and vertical and horizontal analysis. In order to comply with the objectives, the Horizontal and Vertical Analysis of the structure of the Balance Sheet and the Income Statement were performed; through the Vertical Analysis, it was possible to establish the most significant accounts of assets, liabilities, equity, income and expenses, in the Horizontal Analysis, for its part, it allowed the comparison of each of the accounts that make up the balance sheets during the years 2014 and 2015; Likewise, some financial indicators of the PERLAS Monitoring System were applied, which allowed to know in a real way the level of economic and financial profitability of the entity and finally a financial analysis report was prepared with the respective improvement results obtained, the same ones that facilitate the decision making. After concluding the Financial Analysis work in the credit institution and with the results obtained, it was concluded that the Cooperative reflects a stable level of liquidity and profitability, it is recommended to carry out the Financial Analysis in the agencies at least once a year, as well as the application of Financial Indicators that will help to make correct decisions for the growth of the Cooperative in the Financial field.